Hubungan antara Spiritualitas dan Religiusitas dengan Illusion of Control pada Emerging Adult - Louis Sebastian Vigar; Karel Karsten Himawan; Eunike Mutiara (Fakultas Psikologi Universitas Pancasila, 2016)
In Indonesia, gambling activities are having an upward trend. On the other side, Indonesia is a country that based their constitution on law and influenced by religious values, which both clearly prohibit any kind of gambling activities. Moreover, considering that most of Indonesian people are having a religion, some expression and manifestation of religiosity and spirituality should appear in their daily practices and are assumed to be reflected in their negative attitude toward gambling. However, several gambling-related phenomena still occur in many forms. In relation to gambling, one of many factors that might be responsible to the persistence of gambling is the illusion of control. However, it is clear that various religious teachings are emphasizing the existence of control that is bigger than our control, which comes from the Almighty. Therefore, the purpose of this study is to examine empirically whether or not there is a significant relationship between spirituality and religiosity with the illusion of control on emerging adult who conducts gambling in Jakarta and its surrounding areas. The research was participated by 100 students from many universities in Jakarta and the surrounding areas. The sampling method used in this research was snowball sampling. The results showed no significant relationship between spirituality and religiosity with the illusion of control on emerging adult in Jakarta and the surrounding areas. Further analysis on additional data also showed that demographic factors do not provide a significant variation of the results.